Nilai Budaya Folklore Hantu di Era Digital Studi Kasus Channel Youtube Rizky Riplay - Muhammad Maftukhan; Edi Dwi Riyanto (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2022)
Abstract The purpose of this study is to describe the cultural values of ghost folklore in the YouTube content presentation of the Rizky Riplay channel. This research is qualitative by using descriptive method as a problem study of the object under study. Sources of data in this study are videos on Rizky Riplay's youtube channel that present illustrations of ghost storytelling in the form of animation. The data collection technique used in this research is a case study of videos on Rizky Riplay's youtube channel. Data processing techniques in this study include: 1) matching the data from the findings; 2) conduct a systematic review of the data; 3) analyze the findings in accordance with the issues raised for later interpretation into the results of the analysis; 4) drawing conclusions. The results of the analysis show that: first, there are product innovations on Rizky Riplay's youtube channel and the cultural values of ghost folklore that have shifted in the digital era. Not only as an educational and religious value but also as a means of entertainment. Second, Rizky Riplay's Youtube Channel is considered to have made a fortune through the help of ghost animations that are the main characters in each of its content. Third, the ghosts in the form of animations/cartoons are considered to have made youtube channel owners rich by doing endorsements/promotions of products and services for human needs as well as the monetization system from YouTube. Not only as an educational and religious value but also as a means of entertainment. Second, Rizky Riplay's Youtube Channel is considered to have earned wealth through the help of ghost animations that are the main characters in each of its content. Third, the ghosts in the form of animations/cartoons are considered to have made YouTube channel owners rich by doing endorsements/promotions of products and services for human needs and the monetization system from YouTube. Not only as an educational and religious value but also as a means of entertainment. Second, Rizky Riplay's Youtube Channel is considered to have made a fortune through the help of ghost animations that are the main characters in each of its content. Third, the ghosts in the form of animations/cartoons are considered to have made YouTube channel owners rich by doing endorsements/promotions of products and services for human needs and the monetization system from YouTube. Keywords: cultural values, Ghostlore, innovation product, youtube